1983
DOI: 10.2166/wst.1983.0174
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Recalcitrant Organochlorine Compounds in Fixed Film Reactors

Abstract: Biodegradation in fixed film reactors of chloroorganic compounds in kraft bleaching effluent and in pesticides was studied. Specific biofilm reactors could be adapted for the mineralization of chloroform, chlorophenols, chlorocatechols, chloroguaiacols, chloroveratroles and chlorinated resin acids in bleaching effluent and for chlorophenols in spills of pesticides for blue stain and wood rot. Mineralization of chloroorganic compounds into inorganic chloride and carbon dioxide occurred in the solid phase of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Easily degradable soil organic matter has been demonstrated to increase the degradation rate of numerous xenobiotic compounds (Kuwatsuka and Igarshi 1975;Salkinoja-Salonen et al 1983;Valo and Salkinoja-Salonen 1986). High concentrations of nitrogen has been shown to inhibit atrazine and2,4-D mineralization by some mycorrhizal fungi in vitro (Donnelly et al 1993).…”
mentioning
confidence: 99%
“…Easily degradable soil organic matter has been demonstrated to increase the degradation rate of numerous xenobiotic compounds (Kuwatsuka and Igarshi 1975;Salkinoja-Salonen et al 1983;Valo and Salkinoja-Salonen 1986). High concentrations of nitrogen has been shown to inhibit atrazine and2,4-D mineralization by some mycorrhizal fungi in vitro (Donnelly et al 1993).…”
mentioning
confidence: 99%
“…Successful treatment of contaminated wastewater containing chlorinated phenols has been performed in pilot and fi eld-scale studies involving aerobic organisms such as Flavobacterium species and Rhodococcus species (Apajalahti and Sakinoja-Salonen, 1986;Salkinoja-Salonen et al, 1983). In-situ remediation of 2,4,6-TCP studies that were reported previously dealt mainly with soils contaminated with the chlorinated compounds (Baker and Mayfi eld, 1980).…”
Section: Removal Of 246 -Tcp In Sludgementioning
confidence: 99%
“…For instance, biofiltration has been used extensively to remove volatile organic compounds from air emissions (Hodge et al, 1991;Kampbell et al, 1987;Leson and Winer, 1991;Medina et al, 1990, vapor-phase bioreactors have treated chlorinated aliphatics in the gaseous state (Folsom and Chapman, 1991;Shields and Reagin, 19921, and fmed film bioredctors have been used for the treatment of a variety of chlorinated aromatic chemicals (Fathepure and Vogel, 1991;Salkinoja-Salonen et al, 1983) and petroleum refinery effluent (Hamoda and Al-Haddad, 1987). With varying success, reactor technologies have been applied to the treatment of soil and water contaminated with the chemicals found in organic wood preservatives, such as creosote (e.g., PAHs) or pentachlorophenol (PCP) (U.S. EPA, 1991a; Blais, 1988;Mueller et al, 199%).…”
Section: Bioremediation In Reactorsmentioning
confidence: 99%